Particulate Trace Metal Sources, Cycling, and Distributions on the Southwest African Shelf. Issue 11 (14th November 2022) - Al‐Hashem, Ali A.; Beck, Aaron J.; Krisch, Stephan; Menzel Barraqueta, Jan‐Lukas; Steffens, Tim; Achterberg, Eric P.
Abstract: We present labile (L‐pTM) and refractory (R‐pTM) particulate trace metal distributions of Fe, Mn, Al, Ti, Co, Zn, Cd, Ni, Pb, Cu, and P for a transect along the southwest African shelf and an off‐shore section at 3°S of the GEOTRACES GA08 section cruise. Particle sources and biogeochemical cycling processes are inferred using particle‐type proxies and elemental ratios. Enhanced concentrations of bio‐essential L‐pTMs (Zn, Cu, Ni, Cd, Co, and P) were observed in the Benguela upwelling region, attributed to enhanced primary production. Bio‐essential pTM stoichiometric ratios (normalized to pP) were consistent with phytoplankton biomass across the transect, except for Fe and Mn, which included adsorbed and labile oxide phases. Low pP lability (∼41%) suggests a potential refractory biogenic source on the Benguela shelf. Variable labilities observed between stations along the transect indicated potentially different biogenic pP labilities among different plankton groups. Benthic resuspension was prevalent in (near‐)bottom waters along the transect and formed an important source of Fe and Mn oxides. Lithogenic particles along the entire shelf were Mn deficient and particles on the Benguela shelf were enriched in Fe, consistent with regional sediment compositions. Enhanced available‐Fe (dissolved + labile particulate Fe) concentrations (up to 39.6 nM) were observed in oxygen‐deficient (near‐)bottom waters of the Benguela shelf coinciding with low L‐pMn. This was attributed to the faster oxidation kinetics of Fe, allowing Fe‐oxide precipitation and retention on the shelf, while Mn oxidation was slower. Enhanced L‐pFe in the Congo River plume, which comprised as much as 93% of the available‐Fe pool, was attributed to increased scavenging and formation of Fe oxides. Increased scavenging of other particle‐reactive trace metals (TMs) (Mn, Al, and Pb) was also apparent in Congo‐influenced waters. However, particles did not play a significant role in transporting TMs off‐shelf within Congo plume waters. Plain Language Summary: Trace metals (TMs) are important to the functioning of marine ecosystems, with a range of TMs required as micronutrients by phytoplankton, while some are contaminants, and others may serve as tracers of water masses. Marine particles are key to the biogeochemical cycling of most TMs as sources, sinks, and essential transport vectors in the ocean. The transport and fate of TMs are often multi‐faceted and upon a multitude of inter‐related factors including particle sources/types, and environmental conditions, many of which are directly evident on continental shelves. Continental shelves thus are important conduits through which TMs are transferred from land to the ocean. Despite their importance, shelves are still understudied with respect to trace metal cycling. Here we present data from the longest continental shelf transect for TMs to date, which traversed through several key biogeochemical regimes, including an oxygen depleted zone, upwelling region, and a river plume, providing unique gradients under which particles from various sources and internal cycling processes were studied. A chemical leach was applied to marine particles to differentiate between particle types and phases. Utilizing the contrasting marine environments and particle types encountered along the transect, we highlight the major biogeochemical cycling dynamics controlling trace metal distributions, which provide valuable regional insights which may be extended to other regions of the global ocean. Key Points: Different oxidation kinetics lead to decoupled Fe and Mn oxide redox cycling within oxygen‐depleted waters on the Benguela Shelf Lower lability of particulate phosphorus (∼41%) indicate potential refractory biogenic source on Benguela shelf Nepheloid particles formed important sources of Fe and Mn oxides that adsorb trace metals (TMs), and serve as potential TM sources from shelf to open ocean